Investigating the Level of Knowledge of the Community about Oral and Dental Health - BEKİROĞLU, GÜLNAZ NURAL (My University, 2021)
Abstract Objectives This study aimed to determine the knowledge and approaches of the participants about oral and dental health. Materials and Methods This was a questionnaire-based cross-sectional survey. Participants’ demographic characteristics, tooth brushing habits, selection of toothpaste, and reasons for visiting the dentist were examined in this study. Participants’ knowledge levels of fluoride and their attitudes toward the most common fluoride applications among preventive treatments were also evaluated. Data entry and analyses were performed using SPSS statistical software. Descriptive and inferential statistics and chi-square test were used for analyzes. Results A total of 2,744 voluntary participants including 1,938 (70.6%) females and 806 (29.4%) males responded; 1,391 (50.7%) participants know the contents of their toothpaste; 1,680 (61.2%) participants point out that fluoride is effective in preventing dental caries. Female participants reported a statistically significant difference in their knowledge of what is fluoride when compared with male participants (p = 0.0001). The knowledge level of participants who had higher levels of education were statistically significantly different when compared with the participants who had lower education levels about fluoride and fluoride applications (p = 0.0001). Conclusions The results of this study indicate that participants’ attitudes toward oral health and dental care need to be improved.